Dominance of SARS-CoV-2 Delta AY.33 sublineage and Omicron BA.1.1 sublineage in Erbil City/Kurdistan Region of Iraq: Molecular and evolutionary study of SARS-CoV-2 - Abdulaziz, Sazan Moffaq; Ghareeb, Asmaa Ameen; Rahman, Mohammed Omar; Haji, Sayran Hamad (Cellular and Molecular Biology, 2024)
This study aimed to analyze the genetic characteristics of a sample of SARS-CoV-2 strains circulated in Erbil City from the 15th of October 2021 and the 5th of January 2022 focusing on their evolutionary feature including lineages, sublineages and clades. Following confirmation of the SARS-CoV-2 positivity of throat and nasopharyngeal swab specimens using qRT-PCR, 20 RNA extracts were subjected to NGS of the S gene and analysis in which only 12 matched the criteria of good sequences. Later, alignment was done with WIV04 reference sequence from Wuhan applying a number of bioinformatics tools. Then, based on sequences recorded in EpiCoV database/GISAID, related genomes to our sequences were identified. The PANGO system revealed that out of the 12 sequences, 10 were Delta (B.1.617.2) variants and two were Omicron (B.1.1.529). Seven out of 10 Delta sequences belonged to AY.33 sublineage and 2 were AY.4. Both Omicron sequences belonged to BA.1.1 sublineage. All Delta sequences belonged to the 21J Nextstrain subclade, meanwhile, both Omicron sequences were from 21K. Spike protein mutations in Delta variant varied, some were sublineage-specific, and others were unique, however, mutations generally were found in the N-terminal domain. Omicron variant appeared with 33 mutations, most of which were in the receptor-binding domain. On the whole, related sequences to our sequences were from Germany, the USA, Denmark, the UK, Iraq, Turkey and several other countries. These findings could provide insights into SARS-CoV-2 evolution nature and significant impact of amino acid changes in the spike protein on disease pathogenicity and emphasize the demand for continuous genomic surveillance globally.